Pharmacokinetic variability of flecainide in younger Japanese patients and mechanisms for renal excretion and intestinal absorption. (20th November 2013) - Horie, Asuka; Ishida, Kazuya; Shibata, Kaito; Taguchi, Masato; Ozawa, Ayaka; Hirono, Keiichi; Ichida, Fukiko; Hashimoto, Yukiya
ABSTRACT The aims of the present study were to evaluate the variability of pharmacokinetics of flecainide in young Japanese patients and to investigate the mechanisms of renal excretion and intestinal absorption of the drug using cultured epithelial cells. First the plasma concentration data of flecainide was analysed in 16 Japanese patients aged between 0.07 and 18.30 years using a one‐compartment model. Considerable interindividual variability was observed in the oral clearance (CL/F) and the apparent volume of distribution (V/F) of flecainide in the young patients. Flecainide was transported selectively in the basolateral‐to‐apical direction in P‐glycoprotein‐expressing renal epithelial LLC‐GA5‐COL150 cell monolayers. The uptake of flecainide into intestinal epithelial LS180 cells was decreased significantly by acidification of the extracellular medium, and was inhibited by tertiary amines, such as diphenhydramine and quinidine. These findings in the present study suggest that flecainide is excreted by P‐glycoprotein in the renal tubule and is taken up by the postulated H+/tertiary amine antiporter in the intestine, and that functional variability of not only the hepatic drug‐metabolizing enzymes, but also the transporters in the kidney and intestine, may be responsible for the interindividual variability of systemic clearance (CL) and/or the bioavailability (F) of flecainide. Copyright © 2013 John Wiley & Sons, Ltd.